Comparison of parasite loads in serum and blood samples from patients in acute and chronic phases of Chagas disease (2018)
Molecular methods have been developed for the detection and quantification of Trypanosoma cruzi DNA in blood samples from patients with Chagas disease. However, aspects of sample processing necessary for quantitative real-time PCR (qPCR), such as the addition of guanidine hydrochloride to whole blood samples, may limit timely access to molecular diagnosis. We analysed 169 samples from serum and guanidine-EDTA blood (GEB) obtained from patients in acute and chronic phases of Chagas disease. We applied qPCR targeted to the satellite DNA region. Finally, we compared the parasite loads and cycle of threshold values of the qPCR. The results confirmed the usefulness of serum samples for the detection and quantification of parasite DNA in patients with Chagas disease, especially in the acute phase. However, the parasite loads detected in serum samples from patients in the chronic phase were lower than those detected in GEB samples. The epidemiological implications of the findings are herein discussed. © Cambridge University Press 2018.